RANCANGAN ALAT MENDETEKSI ASAP DAN API DENGAN SENSOR (GAS DAN SUHU) MENGGUNAKAN ARDUINO UNO - Yose Rizal; Riswal Hanafi Siregar (CV. Multi Kreasi Media, 2022)
Fire is an event that is not desired by every human being. Fires can result in significant losses, both material and life losses. Every fire process always produces smoke and heat and causes an increase in temperature in a place or room where a fire occurs. While the result of the process of changing the material of a fire is the presence of gas smoke in the form of small particles. Through fire detection technology, fire disasters can be detected early. Because fire detectors work by detecting heat and gas leaks. This tool works when it detects one or more of these indicators. Then the alarm and LED will light up as a warning that there has been a fire in the area where the fire detector is installed. Benefits of being able to solve problems that were usually only handled manually, now with Gas and Temperature sensor systems. This research is entitled Design of a Smoke and Fire Detecting Tool with Sensors (gas and Temperature) Using Arduino Uno, the design of this tool aims to provide spontaneous handling when there is smoke and fire in the room, integrate gas and temperature sensors to detect fire and smoke, Buzzer as a device that produces sound if fire and smoke are detected, which means a fire has occurred, accelerates the handling of fires with Automatic Windows and Automatic Water Pumps. Keywords: Fire, Sensor, Design, Tool, Detection.